THEORETICAL AND METHODOLOGICAL BASIS OF DEVELOPING STUDENTS’ LOGICAL THINKING SKILLS - Khasanova Madinakhan Kabirjan daughter (Ta’lim innovatsiyasi va integratsiyasi, 2026)
Abstract: In the article students logical his/her thinking development theoretical basics and lessons effective organization of reaching modern pedagogical approaches analysis Logical of thinking the essence of it structural components and training in the process place illuminated. Also, J. Piaget, H. Gardner, J. Bruner and L. Vygotsky logical thinking about approaches, scientific views based on education process organization and students his/her thinking formation features studied. Students independent and critical their thoughts in improvement problematic education and interactive of methods importance seeing This is the with together , modern education from technologies use through of learners to know activity increase , analytical thinking skills develop and education efficiency possible .